Algorithm of Nursing Approach in the Prevention of Complications of Bronchial Asthma and Assessment of Its Effectiveness (Eurasian Medical Research Periodical, 2023)
The purpose of the study. Assessment of the effectiveness of the nursing approach in bronchial asthma by training and self - monitoring of patients to develop the qualifications and medical level of nurses according to the nursing approach algorithm for patients with bronchial asthma.